Would you like to enter first with a low-quality good? - Luca Lambertini; Piero Tedeschi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
Using a two-period duopoly model with vertical differentiation, we show that there exists a unique subgame perfect equilibrium where the first entrant supplies a lower quality and gains higher profits than the second entrant. We also prove that this entry sequence is also socially efficient.
Keywords: 330